Mutagenic and/or carcinogenic compounds in meat and meat products: polycyclic aromatic hydrocarbons perspective - E. Oz (Теория и практика переработки мяса, 2022)
Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants posing a great risk to human health due to their mutagenic and/or carcinogenic properties. They are produced from incomplete combustion of a heat source, pyrolysis of organic components, and fat-induced flame formation. Meat and meat products are one of the major sources of PAH exposure. Since PAH intake increases the risk of cancer, understanding the factors affecting PAH formation in meat and meat products is very important within the scope of PAH exposure reduction strategies. In this study, the features and formation of PAHs, the factors affecting the formation of PAH compounds and their reduction/inhibition pathways were reviewed in order to provide a perspective on the presence of PAHs in meat and meat products.